A Quantitative Risk-Averse Model for Optimal Management of Multi-Source Standalone Microgrid with Demand Response and Pumped Hydro Storage - Yongqi Zhao (Energies, 2021)
High renewable energy integrated standalone microgrid requires greater ramping capabilities from other dispatchable resources to compensate for effects of the intermittent and variability of the renewable energy available in the system. To address this, a wind-solar-thermal-hydro-coupled multi-source standalone microgrid (WSTHcMSSM) considering demand response and pumped hydro storage is proposed to maximize the operating profit and get the optimal solution of the multi-source generation system by taking advantage of multi-resource complementarity. In WSTHcMSSM, we present a conditional value-at-credibility (CVaC)-based quantitative risk-averse model for uncertain wind and solar power by thoroughly examining the randomness and fuzziness characteristics. Additionally, the most severe issues caused by wind and solar power fluctuation happen during the peak load, and this paper proposes a load partitioning method to get the time-of-use (TOU) in demand response for peak load shaving. A case study is conducted for the validation of the proposed method. It is found from the study case that the CVaC can well evaluate the uncertainty in WSTHcMSSM with wind and solar integration. Additionally, the WSTHcMSSM can efficiently explore the potential flexibility in multi-source complementarity for promoting the penetration of renewable energy.